Jamaica's find - Havill, Juanita; O'Brien, Anne Sibley (Boston : Scholastic Inc., 1986)
A little girl finds a stuffed dog in the park and decides to take it home. Finders keepers, losers weepers? Jamaica discovers a better way!
460
460
Accelerated Reader AR
Keywords: Lost and found possessions -- Fiction; African Americans -- Fiction; Maine -- Illustrators